ChemInform Abstract: One‐Pot Synthesis of Novel Highly Functionalized Furan‐Based Polyphenolics. Issue 16 (March 2016) - Sousa, Joana L. C.; Talhi, Oualid; Rocha, Djenisa H. A.; Pinto, Diana C. G. A.; Almeida Paz, Filipe A.; Bachari, Khaldoun; Kirsch, Gilbert; Silva, Artur M. S.
Abstract: The reaction of 3‐bromochromones (I) with 1, 3‐dicarbonyl compounds (II) proceeds via DBU‐catalyzed 1, 4‐conjugate addition, furan cyclization, and chromanone ring opening to afford desired furan‐based ortho‐phenols (III).